La relación entre autoestima y el uso de la red social Instagram en los jóvenes de 15 y 19 años de edad (2020)
In recent years, the digital age has had an increasing cavity in our daily lives, not only as a benefit within the workplace, in terms of greater accessibility for people, but also to favor socialization processes through social networks. That is why this research will address the characteristics of the relationship of the social network Instagram with the self-esteem of 5 young participants between 15 and 19 years of age who use the social network, from the city of Bogotá, with a time of use minimum of 6 months, through a qualitative study through an interview, free in order to explore the experience within the Instagram platform. From a social approach, since social networks are considered as a third socialization link, such as Instagram, since they have as a dynamic the social interaction between users through the creation of a personal or professional profile, a construction of the identity through the social network. The link to this platform is aimed at interests, personal tastes and vocational development requirements, this according to the main findings found in this research. Likewise, there are a series of risks which are directed to the loss of control over personal, private information since, they can be supplanted, in addition to this, there is a demand for an expected reaction on the part of users as a form of social approval based on the feeling of satisfaction through the expectation of taste on the platform.